The New Role of Terrorism Today - Stajić, Ljubomir S.; Mirković, Vladan M (Zbornik radova Pravnog fakulteta u Novom Sadu, 2021)
Terrorism is a politically motivated violence that has its roots in the teachings and actions of anarchists. Often understood as a weapon of the weak, terrorism is a means of communication through the exploitation of fear that arises as a result of physical violence. Political motive and purpose determine the theoretical notion of terrorism, while in the specific case, the decision on what a terrorist act is is determined by political interest. Political determinism makes terrorism an ideal means of hybrid warfare which is based on the synergy of numerous individual acts that are compatible with each other and serve the same goal. Considering the complexity of hybrid warfare, the ways in which terrorism can be misused for the purpose of hybrid warfare are also different. The paper describes three terrorism misuse models for this purpose.